Krisis Nasionalisme Generasi Muda di Era Globalisasi: Transformasi Kesadaran Berbangsa melalui Project Based Learning dalam Pembelajaran PPKn - Fatur Ubaidillah; Wahidah Wahidah; Risqi Hartiasih Soetomo (Jurnal Cendekia Pendidikan, 2026)
This study aims to describe the implementation of the Project-Based Learning (PjBL) model in Pancasila and Civic Education (PPKn) classes, as well as to assess the improvement in national and state consciousness among Grade XII students at SMA Al-Hidayah, Banyuates District, during the 2024/2025 academic year, and to identify obstacles encountered during implementation. The study employed a Classroom Action Research (CAR) method conducted over two cycles. The research subjects were 14 Grade XII students. Data collection instruments included tests, observations, questionnaires, and documentation. The results indicate that the implementation of PjBL enhanced students' active engagement, communication skills, collaboration, and awareness of national values, with the average student score rising from 46 at the initial stage to 81 by the second cycle. Primary obstacles—specifically limited prior understanding of PjBL and time constraints—were overcome through intensive guidance and improved strategic management. The PjBL model proved effective in fostering sustained national and state consciousness.